Governance' – in crisis? A cross-disciplinary critical review of three decades of 'governance' scholarship - Horvath, A (Centre for Global Higher Education, University of Oxford, 2017)
Dr Aniko Horvath from the UCL Institute of Education analyses the concept of ‘governance’.